Exploring the prospective role of relationships and psychological distress in postpartum risk of intergenerational continuity of child maltreatment - Langevin, Rachel; Hébert, Martine; Bernier, Annie; Frappier, Jean-Yves (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2022)
Objectives: This prospective longitudinal study aimed to explore the role of family relationships (romantic satisfaction and mother-infant bonding) and psychological distress in the associations between four child maltreatment (CM) subtypes (sexual, physical, and emotional abuse, neglect) and early child abuse potential in young mothers.Methods: A sample of 85 pregnant mothers (18-29 years old) was recruited to complete an online survey at Time 1 (T1); 57 mothers participated at T2 (3 months postpartum). The survey documented experiences of CM, prenatal romantic satisfaction, postnatal psychological distress, mother-infant bonding, and child abuse potential using validated questionnaires.Results: Four sequential mediation models were tested, one for each CM subtype. Results show that a maternal history of CM (all subtypes) was indirectly associated with heightened child abuse potential three months postpartum. All CM subtypes were negatively related to prenatal romantic satisfaction, which was in turn negatively associated with postnatal psychological distress. Postnatal psychological distress was related to lower mother-infant bonding which, in turn, was related to increased child abuse potential. The complete sequential model was significant for physical, sexual, and emotional abuse, while a partial sequence was identified with neglect.Implications: Our results are consistent with theoretical models and empirical findings demonstrating the importance of relational factors and mental health in the intergenerational continuity of CM. While our findings await replication, they emphasize the need to intervene early - during the perinatal period - on mental health and family relationships to interrupt intergenerational cycles of CM in at-risk families.